السياسات الزراعية والتجارية وأثرها على القطاع الزراعي في سورية - محمود, حبيب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث بالتحليل السياسات التجارية والزراعية الحالية في سورية في إطار عملية تحرير التجارة وزيادة الانفتاح على المنافسة الخارجية. كما يدرس انعكاس هذه السياسات وبالتالي أثرها على واقع القطاع الزراعي، من خلال الإشارة إلى الصعوبات والمشاكل الرئيسة المرافقة لتلك السياسات في جوانبها التجارية (الاستيراد والتصدير) والاستثمارية (الاستثمار الزراعي والصناعات الغذائية). وفي نهاية البحث يتم عرض وتحديد لإيجابيات وسلبيات السياسات الزراعية والتجارية على القطاع الزراعي في إطار خطة التنمية. This paper analyses the current trade and agricultural policies in Syria taken within the trend toward liberalizing trade and increasing the openness of the economy to the foreign competition. The paper also examines the impact of these policies on the agricultural sector. The analysis is carried out by highlighting the main difficulties and problems associated with these policies especially in its trade part (exportation and importation) and investment one (agricultural investments and food production industries). The paper concludes with a discussion on the advantages and disadvantages of the trade and agricultural policies on the agricultural sector bearing in mind the intended development plan.